Examining prejudice against asylum seekers in Australia: The role of people smugglers, the perception of threat, and acceptance of false beliefs - Suhnan, A.; Pedersen, A.; Hartley, Lisa (The College of Community Psychologists of the Australian Psychological Society, 2012)
Previous research finds a relationship between prejudice against asylum seekers in Australia and negative ideas invoked through political rhetoric; these include perceptions of threat and the acceptance of false beliefs. In recent years, political debate has also seen an increase in hostility towards people smugglers. In this study, we examine whether the expected link between prejudice and perceptions of threat and false beliefs still holds, and we extend this by examining how people smuggler prejudice affects asylum seeker prejudice. A total of 138 members of the Perth community completed a questionnaire regarding their views on these issues. Regression analyses indicated that all three variables significantly and independently predicted prejudice against asylum seekers. Results also showed that prejudice against people smugglers was significantly higher than prejudice against asylum seekers. Our results are consistent with public political rhetoric on community attitudes regarding this topical issue.